A (s) Poética do professor-artista e a Educação - Gomes, Diego Ribeiro; Sanmartin, Stela Maris (Revista do Colóquio, 2023)
The article reflects the teaching work in Basic Education of artist-teachers, school and artistic production using Luigi Pareyson’s thinking, rehearsing relationships between aesthetic education and training in the work plan and teacher training and approximations between teaching and poetics.